2020
DOI: 10.1136/injuryprev-2019-043402
|View full text |Cite
|
Sign up to set email alerts
|

Approaching autonomous driving with cautious optimism: analysis of road traffic injuries involving autonomous vehicles based on field test data

Abstract: ObjectivesTo examine the patterns and associated factors of road traffic injuries (RTIs) involving autonomous vehicles (AVs) and to discuss the public health implications and challenges of autonomous driving.MethodsData were extracted from the reports of traffic crashes involving AVs. All the reports were submitted to the California Department of Motor Vehicles by manufacturers with permission to operate AV test on public roads. Descriptive analysis and χ2 analysis or Fisher’s exact test was conducted to descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It was determined through an analysis of CA DMV collision reports that most AV crashes result in minor damage to both the AV and the other vehicle, and most of the personal injuries involve back pain (Dixit et al, 2016). Back, head and neck injuries are the most common type of injury, with AV occupants representing 70.83% of those injured (Ye et al, 2021). As safety is considered the primary advantage of AVs, the factors Frontiers in Built Environment frontiersin.org associated with increased crash severity were identified and are depicted in Table 2.…”
Section: Identification and Classification Of Crash Severity Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined through an analysis of CA DMV collision reports that most AV crashes result in minor damage to both the AV and the other vehicle, and most of the personal injuries involve back pain (Dixit et al, 2016). Back, head and neck injuries are the most common type of injury, with AV occupants representing 70.83% of those injured (Ye et al, 2021). As safety is considered the primary advantage of AVs, the factors Frontiers in Built Environment frontiersin.org associated with increased crash severity were identified and are depicted in Table 2.…”
Section: Identification and Classification Of Crash Severity Factorsmentioning
confidence: 99%
“…The Society of Automotive Engineers (SAE) outlines six levels of automation: Level 0 is completely manual, Levels 1 to 3 are partially autonomous, and Levels 4 to 5 are completely autonomous (Favarò et al, 2018). As the level of automation rises, the vehicle requires less human involvement and support to function safely, which minimizes driver-related road traffic hazards (Ye et al, 2021). Regardless of their level of automation, however, safety remains a concern, and extensive testing is performed to ensure that they do in fact drastically reduce the number of accidents.…”
mentioning
confidence: 99%
“…An in-depth investigation revealed that perception-reaction time, inaccurate identification and insufficient path planning were significant causes of AV crashes. Similarly, Song et al (2021) displayed that the most representative pattern in AV crashes was “collision following AV stop”, and Ye et al (2021) estimated traffic injuries involving AVs, which showed that autonomous mode can’t perform better in road traffic safety. From the perspective of vulnerable road users (VRUs), Kutela et al (2022) explored patterns of AV crashes and it was found that crosswalks, intersections, traffic signals and movements of AVs were critical for VRUs-AV related crashes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Automated driving systems are often referred to as "autonomous" (e.g., [4][5][6]) and "automated" (e.g., [1,7,8]).…”
Section: Introductionmentioning
confidence: 99%
“…ere are different methods used in the literature to assess the impacts of AVs including field test experiments [4,21] and simulation [10]. Microscopic simulation is one of the most popular methods in AVs' impact assessment on traffic flow in the literature.…”
Section: Introductionmentioning
confidence: 99%